Crypto currency’s "economic nature" in the light of new monetary theory - Karpunin, Vyacheslav I.; Novashina, Tatiana S. (Nexo Revista Científica, 2021)
The systemic and functional analysis of economic nature of Crypto currency within the modern theory of money is a necessary essential component of the study that allowed the authors to formulate a vision of social and economic model of future international monetary system. The authors consider the substance of money in a dialectic unity of the transformation of forms and spheres of its being. The forms of being of money are: material, monetary, paper, electronic. The spheres of being of money are: social, - the "symbol money"; economic, - the "bank notes"; political and legal, - "monetary units". In this paper we show that money is a financial instrument. Money is a market form of universal claim to a share in the wealth of society. The uncovering of internal intrinsic structure of money allows the authors to show convincingly that a currency, especially a "Crypto currency", cannot have and does not have an "economic nature". In considering the process of historical transformation of international monetary systems, taking into account the real achievements of financial, information, program and social engineering for the creation of a digital "gold" the authors believe that the social and economic model of future international monetary system has received its real approbation.